Representation of native myths and legends and cultural values in the Malaysian tourism promotional brochures - Abdul Razak, Norhanim; Romle, Abd Rahim (MAXWELL Science Publication, 2016)
The primary aim of this study is to explore how native mythological tales have been portrayed in tourism marketing. As part of the assessment this research examines the values ingrained in the native myths and the parts of the traditional stories which have been selected for inclusion and commoditisation in tourism brochures. Content analysis of the representation of myths associated with Mount Kinabalu and the legendary warrior named Monsopiad was carried out. Findings show that Mount Kinabalu’s myth has been included in the brochures published from 1969-2015 while the legend associated with Monsopiad has been represented in the brochures published from 2007-2015. Traditional worldviews and values linked to Kadazan Dusun have been projected in the tourism brochures. The analysis of the stories uncovered specific elements associated with Kadazan Dusun people such as the beliefs in the afterlife and presence of spirits, nature as the source of supernatural occurrences and the notion of bravery consisting of physical strength and spiritual power.It was reflected via the projection of two tales that the Kadazan Dusuns are intimately linked to nature, their ancestors and supernatural worlds.Lastly, the findings of this study contribute to understanding of the representation tourism and mythology by demonstrating that in addition to cultural heritage sites, myths and legends have also been included in the promotion of natural sites and natural resources. Besides, the parts of the mythological tales which have been commoditised in the brochures are the ones that showcase the uniqueness of particular ethnic groups and places.